2021
DOI: 10.1177/26334895211041294
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning patients from outpatient mental health services to primary care: A rapid literature review

Abstract: Background A lack of access to mental health services is a critical barrier to obtaining evidence-based care. One strategy to improve access is to transition stable patients out of mental health specialty services and into primary care, thus opening availability for new patients and those with acute mental health needs. To support these transitions, organizations might explore a range of new practices and implementation strategies. Methods We conducted a rapid literature review to summarize descriptions from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Future research focused on characterizing the mechanisms underlying positive organizational changes (e.g., organizational health, provider self-efficacy) ( Lewis et al, 2021 ; Shapiro et al, 2021 ; Vax et al, 2021 ) as well as the extent to which organizational or implementation metrics have a demonstrated impact on the patient experience (e.g., individualized care; reduced wait times; appropriate care transitions; wraparound services) is needed. Consistent with recent calls for more patient-centered care ( Marchand et al, 2019 ), future research using these systems to characterize the impact of implementation metrics on patient-reported recovery outcomes (cf., administrative claims data) is needed ( Blasi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future research focused on characterizing the mechanisms underlying positive organizational changes (e.g., organizational health, provider self-efficacy) ( Lewis et al, 2021 ; Shapiro et al, 2021 ; Vax et al, 2021 ) as well as the extent to which organizational or implementation metrics have a demonstrated impact on the patient experience (e.g., individualized care; reduced wait times; appropriate care transitions; wraparound services) is needed. Consistent with recent calls for more patient-centered care ( Marchand et al, 2019 ), future research using these systems to characterize the impact of implementation metrics on patient-reported recovery outcomes (cf., administrative claims data) is needed ( Blasi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the best available evidence in the field is a rapid review from 2021 by Blasi et al [63] that identified practices for transitioning stable patients from outpatient mental health services to primary care, and a systematic review from 2006 by Gunn et al [64] that assessed the effects of chronic illness management approaches for patients with depression in primary care. The rapid review by Blasi et al [63] included 11 articles representing six categories of transition practices, with patient engagement as the most commonly described transition practice, followed by shared treatment planning, assessment of recovery and stability, care coordination, follow-up and support, and medication management. However, the review did not draw conclusions about best practices or the importance of specific transition processes or strategies, including interventions that promotes recovery for patients transitioning.…”
Section: Existing Evidence On Recovery From Major Depressive Disorder...mentioning
confidence: 99%
“…However, the review did not draw conclusions about best practices or the importance of specific transition processes or strategies, including interventions that promotes recovery for patients transitioning. In addition, the authors may have missed some relevant articles due to the rapid review timeline for literature searching and study selection [63]. The systematic review by Gunn et al [64] found that system level interventions in primary care can led to a modest increase in recovery from depression.…”
Section: Existing Evidence On Recovery From Major Depressive Disorder...mentioning
confidence: 99%
See 1 more Smart Citation
“…(7,12) A review conducted by the National Institute for Health and Care Excellence found no high-quality evidence with outcomes related to successful transitions to a lower level of support. (13) Blasi and colleagues (14) conducted a rapid review of the existent literature on discharge from SCSs to PCPs; however, limitations to this review are the limited number of databases searched and broad outpatient populations. Kim and colleagues (15) intended to conduct a scoping review of barriers and facilitators for transitions from specialty mental health services to primary care from the years 2000-2016.…”
Section: Introductionmentioning
confidence: 99%